ANALYSIS OF CUSTOMER SATISFACTION WITH THE QUALITY OF SERVICE AT DJENG NARA UDUK RICE IN BANGKINANG CITY USING IMPORTANCE PERFORMANCE ANALYSIS (IPA) METHOD - Ena Lidiawati; Librina Tria Putri; Molli Wahyuni (Jurnal Riset Manajemen Indonesia, 2022)
This study aims to determine the level of customer satisfaction with service quality at Nasi Uduk Djeng Nara in Bangkinang Kota using the importance-performance analysis (IPA) method. Importance-performance analysis (IPA) is an analysis of the level of conformity of customer expectations with the performance or reality received by the customer. The population in this study were customers who ate Nasi Uduk Djeng Nara Bangkinang Kota using unknow populations. From the results of the calculation of the unknow population, there were 97 samples. Based on the results of the study, it shows that overall customers are satisfied with the quality of service provided by Nasi Uduk Djeng Nara in Bangkinang Kota as evidenced by the processed data which shows that more statement items enter the C quadrant, as many as 13 (thirteen) items.